Long‐term hydrologic recovery after wildfire and post‐fire forest management in the interior Pacific Northwest. Issue 5 (8th January 2020) - Niemeyer, Ryan J.; Bladon, Kevin D.; Woodsmith, Richard D.
Abstract: Elevated wildfire activity in many regions in recent decades has increased concerns about the short‐ and long‐term effects on water quantity, quality, and aquatic ecosystem health. Often, loss of canopy interception and transpiration, along with changes in soil structural properties, leads to elevated total annual water yields, peak flows, and low flows. Post‐fire land management treatments are often used to promote forest regeneration and mitigate effects to terrestrial and aquatic ecosystems. However, few studies have investigated the longer‐term effects of either wildfire or post‐fire land management on catchment hydrology. Our objectives were to quantify and compare the short‐ and longer‐term effects of both wildfire and post‐fire forest management treatments on annual discharge, peak flows, low flows, and evapotranspiration (AET). We analyzed ten years of pre‐fire data, along with post‐fire data from 1 to 7 and 35 to 41 years after wildfire burned three experimental catchments in the Entiat Experimental Forest (EEF) in the Pacific Northwest, USA. After the fire, two of the catchments were salvage logged, aerially seeded, and fertilized, while the third catchment remained as a burned reference. We observed increases in annual discharge (150–202%), peak flows (234–283%), and low flows (42–81%), along with decreases in AET (34–45%), across all three study catchments in the first seven year period after the EEF wildfire. Comparatively, annual discharge, peak flows, lows flows, and AET had returned to pre‐fire levels 35–41 years after the EEF fire in the two salvage logged and seeded catchments. Surprisingly, in the catchment that was burned but not actively managed, the annual discharge and runoff ratios remained elevated, while AET remained lower, during the period 35–41 years after the EEF fire. We posit that differences in long‐term hydrologic recovery across catchments were driven by delayed vegetation recovery in the unmanaged catchment. Our study demonstrates that post‐fire land management decisions have the potential to produce meaningful differences in the long‐term recovery of catchment‐scale ecohydrologic processes and streamflow. Abstract : Our study revealed elevated discharge and suppressed evapotranspiration (AET) 35–41 years in a catchment (Fox Creek) that was burned but not actively managed post‐fire. Conversely, discharge and AET returned to pre‐fire levels in two catchments (Burns and McCrea Creeks) that were burned, salvage logged, seeded, and fertilized. This study demonstrated that wildfire and post‐fire forest management can impact hydrological processes over 40 years after a wildfire.